Allosteric modulation of metabotropic glutamate receptors by chloride ions. Issue 10 (26th June 2015) - Tora, Amélie S.; Rovira, Xavier; Dione, Ibrahima; Bertrand, Hugues‐Olivier; Brabet, Isabelle; De Koninck, Yves; Doyon, Nicolas; Pin, Jean‐Philippe; Acher, Francine; Goudet, Cyril
ABSTRACT: Metabotropic glutamate receptors (mGluRs) play key roles in the modulation of many synapses. Chloride (Cl ‐ ) is known to directly bind and regulate the function of different actors of neuronal activity, and several studies have pointed to the possible modulation of mGluRs by Cl ‐ . Herein, we demonstrate that Cl ‐ behaves as a positive allosteric modulator of mGluRs. For example, whereas glutamate potency was 3.08 ± 0.33 μM on metabotropic glutamate (mGlu) 4 receptors in high‐Cl ‐ buffer, signaling activity was almost abolished in low Cl _ in cell‐based assays. Cl ‐ potency was 78.6 ± 3.5 mM. Cl ‐ possesses a high positive cooperativity with glutamate (Hill slope ã6 on mGlu4), meaning that small variations in [Cl ‐ ] lead to large variations in glutamate action. Using molecular modeling and mutagenesis, we have identified 2 well‐conserved Cl ‐ binding pockets in the extracellular domain of mGluRs. Moreover, modeling of activity‐dependent Cl ‐ variations at GABAergic synapses suggests that these variations may be compatible with a dynamic modulation of the most sensitive mGluRs present in these synapses. Taken together, these data reveal a necessary role of Cl ‐ for the glutamate activation of manymGluRs. Exploiting Cl ‐ binding pockets may yield to the development of innovative regulators of mGluR activity.—Tora, A. S., Rovira, X., Dione, I., Bertrand, H.‐O., Brabet, I., De Koninck, Y., Doyon, N., Pin, J.P., Acher, F., Goudet, C. Allosteric modulation of metabotropic glutamate receptors by chloride ions. FASEB J. 29, 4174‐4188 (2015). www.fasebj.org